Nest-site selection, territory quality and breeding performance in a Blue Tit Cyanistes caeruleus population - Maícas, Ramón; Muriel, Jaime; Bonillo, Juan Carlos; Fernández Haeger, Juan (Acta Oecologica, 2012)
Patterns of territory selection and sources of variation for reproductive performance in a Blue Tit Cyanistes caeruleus population breeding in nest-boxes during years 2007 and 2008 in a holm oak forest are analyzed. Territory selection has been assessed as a function of two ﬁxed effect factors: territory location (peripheral vs. interior in the nestbox patch) and nestbox type (entrance hole: 26 mm vs. 32 mm). Breeding density was independent of these factors. Pairs nesting in periphery nest-boxes and in smallholed nestboxes owned territories bigger than those nesting in interior and large-holed nestboxes, respectively. The breeding traits studied were laying date, clutch size, hatching success, ﬂedgling success and breeding success. Egg laying was earlier in periphery territories and small-holed nestboxes. Between-year variation was a factor signiﬁcantly affecting to all breeding traits. Clutch size declines in late clutches. Hatching success was higher in territories with more tree density. Although egg laying started earlier in some territories, the mean breeding success was similar in all of them. However, territories with the greatest contribution of individuals to the population were those with small-holed nestboxes. Breeding success in successful pairs had a tendency to be higher in pairs with late clutches and in those nesting in interior territories with large-holed nestboxes. Both decreased breeding success and total breeding failure were much more important in the second breeding year than in the ﬁrst one. The high breeding density of Blue Tit, favored by the experimental design of nestbox plot, did not suggest signiﬁcant variation between territories in terms of breeding success achieved. Implications for nestbox management are discussed.
Keywords: Blue tit; Breeding performance; GIS; Holm oak forest; Nest-site selection; Territory quality

Wood provisioning in Mediterranean forests: A bottom-up spatial valuation approach - Ojea, Elena; Ruíz-Benito, PALOMA; Markandya, Anil; Zavala, MIGUEL a (Forest Policy and Economics, 2012)
The science of ecosystem services has evolved signiﬁcantly in the last decade following an increase in interest in the understanding and valuation of these services. Forests provide important ecosystem services that supply societal needs, such as timber, but this provision is not free of conﬂicts derived from the intensive management of forests. A GIS based approach using data from national forest inventories allows us to identify the provision of timber services and to conduct its valuation. The analysis includes a sample of 37,761 plots for 38 commercial tree species in the Spanish Mediterranean region, where we identify sustainable and nonsustainable forests in terms of harvesting intensities and value both the ﬂow of beneﬁts and their net present value. From the analysis we conclude that non-sustainable forests are providing higher economic returns than sustainable forests for most abundant tree species. However, when analysing long term trends, results show that sustainable forests yield higher economic beneﬁts. This latter perspective is preferred when looking at the value of timber as a provisioning service of forests. According to our results, if we wish to encourage sustainability we need to (a) get lower discount rates adopted for the private sector and (b) ensure longer time horizons.
The following values have no corresponding Zotero field: publisher: Elsevier B.V.
Keywords: Economic valuation; GIS; mediterranean forest; Non-sustainable harvest; Sustainable harvest; Timber provisioning

Main landscape metrics affecting abundance and diversity of game species in a semi-arid agroecosystem in the Mediterranean region - Belda, A.; Martinez-Perez, J. E.; Peiro, V.; Seva, E.; Argues, J. (SPANISH JOURNAL OF AGRICULTURAL RESEARCH, 2011)
Hunting bags provide important information for conservation measures and wildlife management. This study is to assess relationships between landscape structure and game species. The community parameters (abundance, richness and diversity) and landscape/land use indices have been related, using GIS and statistical analysis, in the South-East of Spain (Marina Baja, Alicante). Game species richness (S) is determined by the presence of fruit groves (p = 0.001, R = 0.714) and landscape shape. The total density of species (TD) is influenced positively by fruit groves (p = 0.001, R = 0.783) and wooded shrublands (p = 0.002, R = 0.911), but is influenced negatively by urban areas (p < 0.001, R = 0.844). Small game communities correlate to irrigated fruit (p = 0.002, R = 0.754) and dry vineyard (p = 0.021, R = 0.839) and also with the diversity landscape index (p = 0.029, R = 0.708). Big game density is positively related to holm oak (p = 0.018, R = 0.812) and dense pine forests (p = 0.001, R = 0.849) and also with the total area landscape index (p = 0.011, R = 0.921). Population control species prefer irrigated fruit (p < 0.001, R = 0.775), fruit groves (p < 0.001, R = 0.857) and irrigated vineyard (p = 0.017, R = 0.833) land uses. Our conclusion is that most game species presents a positive relation with landscape structure, such as fractal dimension and shape index, and traditional agriculture based on irrigated and dry fruit crops.
The following values have no corresponding Zotero field: pub-location: AUTOPISTA A-6, KM 7 5, MADRID, 28040, SPAIN publisher: SPANISH NATL INST AGRICULTURAL & FOOD RESEARCH & TECHNOLO
Keywords: game community; GIS; hunting bags; Mediterranean agrosystem; semi-arid climate

Potential of biomass residues for energy production and utilization in a region of Portugal - Fernandes, U.; Costa, M. (Biomass and Bioenergy, 2010)
This article concentrates on the evaluation of the potential of biomass residues, both forest and agricultural residues, for energy production and utilization in a region of Portugal (Marva˜o). Marva˜o has been identiﬁed as an excellent region for the installation of smallscale biomass plants for heating purposes given the relatively high potential of biomass residues that it presents. The assessment of the potential of the biomass residues was carried out using Geographical Information Systems (GIS) database and statistical analysis. It was concluded that the annual biomass residues potential for Marva˜o is about 10,600 tonnes, which corresponds to an energy production potential of about 106,000 GJ per annum. In addition, to illustrate the potential of biomass residues for energy utilization in the region of Marva˜o, the heating system of a hotel located in Marva˜o village has been analyzed as a case study. It was concluded that the conversion of the existing fossil fuelbased heating system to a biomass-based system would have economical and environmental advantages for local investors.
The following values have no corresponding Zotero field: publisher: Elsevier Ltd
Keywords: Biomass residues; Energy potential; GIS; Pellets boiler

Quantitatively defining the conservation status of Natura 2000 forest habitats and improving management options for enhancing biodiversity - Hernando, Ana; Tejera, Rosario; Velazquez, Javier; Núñez, María Victoria (Biodiversity and Conservation, 2010)
The main goal of Natura 2000 network is to guarantee the favourable conservation status of habitats and species ensuring European biodiversity. As a result, certain forest areas have been included in this network listed as 9230-Quercus pyrenaica habitat and 9340-Quercus ilex subsp. rotundifolia forest habitat. These areas were previously used for ﬁrewood extraction or livestock grazing and browsing. Nowadays these habitats are coppice forests with asexual regeneration, which is far from the desired conservation status. Traditional timber harvesting plans do not take account of the new objectives required for these Natura sites, which attempt to ensure biodiversity and recreational uses instead of simply focusing on timber production. This paper proposes a ﬂexible methodology (applied to the study area ‘‘Dehesa Boyal’’ in A´ vila, Spain) for managing Natura 2000 forest sites by stands for sustainable forest management and the new requirements. The methodology has two phases. The ﬁrst, ‘‘Division of the forest area into stands’’, deﬁnes homogeneous patches of vegetation distinct in species composition, physiognomic structure and future management. The second, ‘‘Conservation status assessment of stands’’, quantiﬁes the conservation status of each previously classiﬁed stand considering a series of factors such as: functional health, restoration, ﬂoral richness and structure. A total value integrating the conservation status of stands is then calculated for the habitat. Both phases use Geographic Information System tools for managing information and visualizing results. The proposed methodology provides forest managers with a good knowledge of the territory and subsequently enables them to take appropriate conservation measures to maintain biodiversity.
Keywords: Adaptive management; Asexual regeneration; Cattle; Coppice forest; GIS; Mediterranean biogeographic region; oak; Quercus pyrenaica; Spain; Stand

A map of autumn precipitation for the third millennium BP in the Eastern Iberian Peninsula from charcoal carbon isotopes - Aguilera, M.; Espinar, C.; Ferrio, J. P.; Pérez, G.; Voltas, J. (Journal of Geochemical Exploration, 2009)
Carbon isotope composition (δ 13 C) in tree-rings has become routinely used in palaeoclimatic research for the assessment of changes in plant water availability in seasonally dry climates. However, the distribution of long tree-ring records around the world is very limited. Alternatively, the original climate signal of wood δ 13 C is well preserved in fossil charcoal and, accordingly, charcoal δ 13 C can be used to quantify past changes in water availability (e.g. precipitation). We report a case study on spatial palaeoclimate reconstruction which aims to characterize the transition between Bronze and Iron Ages, the so-called Iron Age Cold Epoch (ca. 900– 300 BCE), using charcoals of Quercus ilex/coccifera from a set of 11 contemporary archaeological sites of eastern Spain. Climatic inferences were obtained after calibrating a linear model predicting seasonal precipitation from δ 13 C of Q. ilex wood samples obtained across a rainfall gradient. The best regression model corresponded to September–December (autumn) precipitation (Paut ), in agreement with the fact that Q. ilex is able to exploit previous-year water reserves thanks to very effective water uptake. Subsequently, we estimated Paut from the δ 13 C of fossil charcoal to infer spatial patterns in water availability. Overall, estimated past Paut was about 19% higher (296 mm) than present-time values averaged across archaeological sites (249 mm). However, a clear geographic pattern of differences in precipitation could be observed in which the inner continental regions of eastern Spain were characterized by more humid conditions in the past, whereas the coastal strip of the Mediterranean Sea barely differed in past and present Paut values. The quite uniform distribution of archaeological sites over eastern Spain allowed development of contour maps of absolute and relative (to present) past Paut using gridded interpolation methods implemented in a GIS, highlighting the potential of this approach for reconstructing high-resolution spatial patterns of past climate
The following values have no corresponding Zotero field: publisher: Elsevier B.V.
Keywords: Drought; GIS; Iron Age Cold Epoch; Isoscape; Late Holocene; Mediterranean climate; Quercus ilex

Avaliação do Potencial de Actividades em Sistemas de Uso Múltiplo: Aptidão Forrageira - Alpendre, Pedro; Gonçalves, Ana Cristina; Ferreira, Alfredo Gonçalves; Dias, Susana Saraiva (Silva Lusitana, 2008)
Multiple use systems are characterised by the presence of several cultures in a management unit. These cultures present their own characteristics and several productions, with different spatial and temporal arrangements. In Alentejo the most representative systems, in terms of area, are the "montados", agro-silvo-pastoral systems, characterised by three main components, forest, agriculture and grazing, and the interrelations among them. In these systems the grazing component and, consequently, the pasture is a fundamental activity for the system maintenance/perpetuity. The goal of this study is to create a methodology that defines the forage aptitude of the "montado", as function of the soil and forest cover. The utilisation of spatial analysis processes, in geographical information systems, allowed the development of an innovative methodology, constituting an evaluation and implementation information tool.
The following values have no corresponding Zotero field: publisher: scielopt
Keywords: activités en systèmes d; aptitude de; evaluation du potentiel des; evaluation tool; forage aptitude; forest cover; GIS; les systèmes d; par la présence de; plusieurs cultures; production fourragère; résumé; soils; usage multiple; usage multiple sont caractérisés

Avaliação do Potencial de Actividades em Sistemas de Uso Múltiplo: Aptidão Forrageira - Alpendre, Pedro; Gonçalves, Ana Cristina; Ferreira, Alfredo Gonçalves; Dias, Susana Saraiva (Silva Lusitana, 2008)
Multiple use systems are characterised by the presence of several cultures in a management unit. These cultures present their own characteristics and several productions, with different spatial and temporal arrangements. In Alentejo the most representative systems, in terms of area, are the "montados", agro-silvo-pastoral systems, characterised by three main components, forest, agriculture and grazing, and the interrelations among them. In these systems the grazing component and, consequently, the pasture is a fundamental activity for the system maintenance/perpetuity. The goal of this study is to create a methodology that defines the forage aptitude of the "montado", as function of the soil and forest cover. The utilisation of spatial analysis processes, in geographical information systems, allowed the development of an innovative methodology, constituting an evaluation and implementation information tool.
Keywords: activités en systèmes d; aptitude de; evaluation du potentiel des; evaluation tool; forage aptitude; forest cover; GIS; les systèmes d; par la présence de; plusieurs cultures; production fourragère; résumé; soils; usage multiple; usage multiple sont caractérisés

Effects of grazing and topography on long-term vegetation changes in a Mediterranean ecosystem in Israel - Carmel, Yohay; Kadmon, Ronen (Plant Ecology, 1999)
The dynamics of Mediterranean vegetation over 28 years was studied in the Northern Galilee Mountains, Israel, in order to identify and quantify the major factors affecting it at the landscape scale. Image analysis of historical and current aerial photographs was used to produce high resolution digital vegetation maps (pixel size = 30 cm) for an area of 4 km2 in the Galilee Mountains, northern Israel. GIS tools were used to produce corresponding maps of grazing regime, topographic indices and other relevant environmental factors. The effects of those factors were quantiﬁed using a multiple regression analyses. Major changes in the vegetation occurred during the period studied (1964–1992); tree cover increased from 2% in 1964 to 41% in 1992, while herbaceous vegetation cover decreased from 56% in 1964 to 24% in 1992. Grazing, topography and initial vegetation cover were found to signiﬁcantly affect present vegetation patterns. Both cattle grazing and goat grazing reduced the rate of increase in tree cover, yet even intensive grazing did not halt the process. Grazing affected also the woody-herbaceous vegetation dynamics, reducing the expansion of woody vegetation. Slope, aspect, and the interaction term between these two factors, signiﬁcantly affected vegetation pattern. Altogether, 56% and 72% of the variability in herbaceous and tree cover, respectively, was explained by the regression models. This study indicates that spatially explicit Mediterranean vegetation dynamics can be predicted with fair accuracy using few biologically important environmental variables.
Keywords: aerial photographs; GIS; landscape ecology; regression model; spatial structure; Vegetation dynamics

Effects of grazing and topography on long-term vegetation changes in a Mediterranean ecosystem in Israel - Carmel, Yohay; Kadmon, Ronen (Plant Ecology, 1999)
The dynamics of Mediterranean vegetation over 28 years was studied in the Northern Galilee Mountains, Israel, in order to identify and quantify the major factors affecting it at the landscape scale. Image analysis of historical and current aerial photographs was used to produce high resolution digital vegetation maps (pixel size = 30 cm) for an area of 4 km2 in the Galilee Mountains, northern Israel. GIS tools were used to produce corresponding maps of grazing regime, topographic indices and other relevant environmental factors. The effects of those factors were quantiﬁed using a multiple regression analyses. Major changes in the vegetation occurred during the period studied (1964–1992); tree cover increased from 2% in 1964 to 41% in 1992, while herbaceous vegetation cover decreased from 56% in 1964 to 24% in 1992. Grazing, topography and initial vegetation cover were found to signiﬁcantly affect present vegetation patterns. Both cattle grazing and goat grazing reduced the rate of increase in tree cover, yet even intensive grazing did not halt the process. Grazing affected also the woody-herbaceous vegetation dynamics, reducing the expansion of woody vegetation. Slope, aspect, and the interaction term between these two factors, signiﬁcantly affected vegetation pattern. Altogether, 56% and 72% of the variability in herbaceous and tree cover, respectively, was explained by the regression models. This study indicates that spatially explicit Mediterranean vegetation dynamics can be predicted with fair accuracy using few biologically important environmental variables.
Keywords: aerial photographs; GIS; landscape ecology; regression model; spatial structure; Vegetation dynamics

Scaling up the biogenic emissions from test sites at Castelporziano - Lenz, Roman; Selige, Thomas; Seufert, Günther (Atmospheric Environment, 1997)
On the basis of measurements of emission rates, Leaf Area Indices (LAI) and biometric data for 17 species and 15 land-cover types, a first scaling up of biogenic emissions for the Castelporziano test site is elaborated It includes the application of different procedures for scaling up, by combining parameters (e.g. LAI, biomass, vegetation coverage, canopy layering, insolation) with emission rates and algorithms in a spatial model. This approach consists of the following steps: (i) elaboration of a pseudo-3D Geographical Information System (GIS) for the test site St. Quercio, and 2D GIS for pseudosteppe, dunes and whole Castelporziano, (ii) calculations of relations between diameter at breast height (dbh), biomass and LA1 from literature and our own data, at St. Quercio, (iii) application of an insolation model in the stands for one to two canop:y layers and surfaces in a l/4 square meter resolution, at St. Quercio; (iv) classified incoming light is driving the emissions of monoterpenes from Stone pine and Holm oak at the test site St. Quercio. For temperature we do not scale up and apply any algorithm to date, but we can show some preliminary surface temperature data from remote sensing activities, possibly to be used during further campaigns. Calculations of total emission fluxes are intercompared for the test site St. Quercio according to the different calculation rules, e.g. the relevancy of spatial effects. The differences between the biomass-based fluxes and the LAI-based fluxes are in the range of 5-30%. The application of the GIS model for light interception for the pine canopy, and for’two canopy layers for Holm oak, is shown for the open stands at St. Quercio. The resulting biogenic emissions are in good accordance with the ones calculated only via biomass or LAI, and the lower parts of a crown seem to be negligible in terms of biogenic emissions.
Keywords: Biogenic emissions; geographical information system; GIS; Land Cover; light interception; scaling up; spatial modelling; Vegetation